Effects of five common preparatory approaches on grand jeté biomechanics - Weigand, V.; Mokha, G. M. (Journal of Dance Medicine & Science, 2024)
Introduction: The grand jeté requires grace and proper biomechanics to produce the iconic glide through the air. Understanding how the preceding choreographed movements affect take-off and flight may influence teaching and training. We sought to examine the effects of 5 common preparatory approaches on grand jeté biomechanics.